2015
DOI: 10.3340/jkns.2015.57.6.460
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral C1 Lateral Mass and C2 Pedicle Screw Fixation for Atlantoaxial Instability in Rheumatoid Arthritis Patients: Comparison with the Bilateral Method

Abstract: ObjectiveBilateral C1 lateral mass and C2 pedicle screw fixation (C1LM-C2P) is an ideal technique for correcting atlantoaxial instability (AAI). However, the inevitable situation of vertebral artery injury or unfavorable bone structure may necessitate the use of unilateral C1LM-C2P. This study compares the fusion rates of the C1 lateral mass and C2 pedicle screw in the unilateral and bilateral methods.MethodsOver five years, C1LM-C2P was performed in 25 patients with AAI in our institute. Preoperative studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A study by Paik et al [15] reported that from the perspective of biomechanics, unilateral C1 lateral mass screw combined with C2 pedicle screw fixation was also an effective technique for patients with atlantoaxial instability and an anatomical variation for whom the screws could not be placed bilaterally.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Paik et al [15] reported that from the perspective of biomechanics, unilateral C1 lateral mass screw combined with C2 pedicle screw fixation was also an effective technique for patients with atlantoaxial instability and an anatomical variation for whom the screws could not be placed bilaterally.…”
Section: Resultsmentioning
confidence: 99%
“…The patient successfully underwent a left-sided C1/C2 pedicle screw fusion alone. [ 6 ] The authors determined that decompression alone was warranted as the cyst did not significantly compress the cord and the mild “short-term” myelopathy would likely resolve with spontaneous cyst regression. Following the unilateral C1–C2 fusion, the patient neurologically improved and remained stable/fused 3 months later [ Figures 2 and 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of VAI during C1 LMS placement has been reported up to 5.8% [14,15]. When asymmetry or unilateral occlusion is present or in the inevitable situation of VAI or in the case of unfavorable bone structures in upper cervical surgery, C1 LMS-C2 PS fixation cannot be performed using the bilateral method even though it results in greater rigidity than the unilateral method [8]. Then, unilateral fixation may be acceptable, but the patient requires an external orthosis until a fusion or bone union achieved [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, they still carry potential risks of injuring the surrounding neurovascular tissue, especially vertebral artery injury (VAI). Furthermore, in the inevitable situation of VAI or in the case of unfavorable bone structures, C1 LMS-C2 PS fixation cannot be performed using the bilateral method [8]. Then, unilateral fixation is generally acceptable, but the patient requires an external orthosis until fusion or bone union is achieved [9].…”
Section: Introductionmentioning
confidence: 99%